Needs and demands of prosthetic treatment among two groups of individuals - Mukatash Gadeer; Al-Rousan Medyan; Al-Sakarna Basma (Wolters Kluwer Medknow Publications, 2010)
Objectives: The level of knowledge, awareness, and attitude about teeth-replacement options among a group of medical and paramedical subjects and to compare them with the general population. Materials and Methods: A self-administered questionnaires using simple Arabic language were distributed to two groups of subjects. Questions focused on the willingness to replace the missing teeth, the preferable methods of choice for replacement, and the reasons for these choices. The first group (G-I) was from the medical and paramedical staff who work in a military hospital at Jordan Royal medical services, the dental staff was excluded from the study. The other group (G-II) was from the general population who attended the dental department in the same hospital with comparable level of education. All the participants were partially edentulous excluding the third molars. Clinical examination was done by qualified prosthodontist to evaluate the possible prosthetic treatment options for replacement. A total of 612 questionnaires were distributed, of which 533 questionnaires were returned (response rate 87.09%). The results were analyzed and comparison was made between the two groups. Results: Responses to questions about awareness and attitude about prosthetic management of missing teeth revealed that G-I have more awareness than G-II to the probable causes for tooth/teeth replacement and limitation of the preferable method for replacement (P<0.05). More than 80% of the participants believed that replacement of anterior teeth is more important than the posterior teeth. Implants and fixed partial denture (FPD), respectively, were more preferable than removable prosthesis, although clinically was not indicated in cases (P<0.05). There was no clinical benefit from replacement of missing teeth in 33.4% while only 6% believe this. Conclusions: This study showed that the awareness and attitude between the medical and paramedical staff to prosthetic needs is better than between general populations. The demands for dental replacement by patients were significantly different when compared with the actual needs.